Hypothermia Protects against Ischemic Stroke through Peroxisome-Proliferator-Activated-Receptor Gamma. (14th July 2022) - Shao, Shuai; Lu, Tian-Yi; Zhang, Jian-Song; Wang, Wen-Jun; Zhang, Xiao-Hua; Chen, Kui; Jia, Feng
Abstract : Ischemic stroke (IS) remains a global public health burden and requires novel strategies. Hypothermia plays a beneficial role in central nervous system diseases. However, the role of hypothermia in IS has not yet been elucidated. In this study, we determined the role of hypothermia in IS and explored its underlying mechanisms. The IS phenotype was detected based on infarct size, infarct volume, and brain edema in mice. Neuroinflammation was evaluated by the activation of microglial cells and the expression of inflammatory genes after ischemia/reperfusion (I/R) and oxygen-glucose deprivation/reperfusion (OGD/R). Neuronal cell apoptosis, cleaved caspase-3 and Bax/Bcl-2 expressions, cell viability, and lactate dehydrogenase (LDH) release were detected after I/R and OGD/R. Blood–brain barrier (BBB) permeability was calculated based on Evans blue extravasation, tight junction protein expression, cell viability, and LDH release after I/R and OGD/R. The expression of peroxisome proliferator-activated receptor gamma (PPAR γ ) was assessed after OGD/R. Our results suggested that hypothermia significantly reduced infarct size, brain edema, and neuroinflammation after I/R. Hypothermia increased PPAR γ expression in microglial cells after OGD/R. Mechanistic studies revealed that hypothermia was a protectant against IS, including attenuated apoptosis of neuronal cells and BBB disruption after I/R and OGD/R, by upregulating PPAR γ expression. The hypothermic effect was reversed by GW9662, a PPAR γ inhibitor. Our data showed that hypothermia may reduce microglial cell-mediated neuroinflammation by upregulating PPAR γ expression in microglial cells. Targeting hypothermia may be a feasible approach for IS treatment.